Performance Analysis of Gamma-Gamma Fading FSO MIMO Links With Pointing Errors - Bhatnagar, Manav R.; Ghassemlooy, Zabih (Journal of lightwave technology, 2016)
The bit error rate (BER) performance of the free space optical (FSO) link suffers from the atmospheric turbulence. By employing additional transmit and receive apertures at the transmitter and receiver, respectively, the error rate of the FSO communication system can be significantly improved. However, the pointing errors (PEs), generated because of the building sway, have the potential to eradicate the benefits of the multiple transmit and/or receive apertures-based FSO communication system. Therefore, for a general and realistic study of the FSO multiple-input multiple-output (MIMO) system, the effect of PEs in the Gamma-Gamma (GG) fading atmospheric fluctuations is considered in this paper. We study two schemes for the FSO MIMO systems: 1) equal gain combining (EGC), and 2) maximal ratio combining (MRC). A new power series-based representation is proposed for the probability density function of the GG fading FSO links with PEs. This new series representation contains only the terms with exponent of the random variable (RV) as compared to the closed-form representation, which contains the Meijer-G function of the RV. Then, we derive the average BER for both combining schemes over the GG fading FSO links with PEs. By using the derived BER expressions, we derive the asymptotic BER for both schemes. The analytical diversity order and combining gains for both systems are also obtained. The effect of PEs over the performance of the schemes is analyzed under different scenarios and it is observed that the PEs significantly degrade the diversity of the FSO MIMO system. It is deduced by simulation and analysis that though the EGC scheme is simpler to implement in practice but the MRC scheme is more rugged to the large PEs.